Evaluasi Keakuratan Kodifikasi Diagnosis Penyakit Mata Menggunakan Aplikasi Kodifikasi Diagnosis Penyakit Mata Berbasis Dekstop Di Klinik Malang Eye Center - Endang Sri Dewi Hastuti Suryandari Suryandari; Fristara Alintia; Hartaty Sarma Sangkot; Avid Wijaya (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
An accuration code of diagnosis disease should match ICD-10 classification. The accuration of diagnosis code of eye diseases at Malang Eye Center Clinic by using code list in excel program was 30%. The purpose of this study was to determine the level of accuracy of the coding of eye diseases before and after using the application of Desktop-based Eye Disease Codes, at Malang Eye Center Clinic. The research design used the Research and Development (R&D) method with the One Group Pretest Posttest approach. This research used 200 outpatient medical record documents (MRD) of eye disease (100 MRD for pretest and 100 MRD for posttest), that were taken using simple random sampling method. The percentage result of the accuracy of the codification of eye disease diagnosis using a desktop-based application is 96%. The results showed that there was a difference in the accuration of diagnosis code of eye diseases before and after using the application of Desktop-based Eye Disease Codes (the Z calculated value was -4.76). This application can be used as a tool for coding officers to code eye diseases at the Malang Eye Center Clinic